Legal Perspective on Foreign Direct Investment and Economic Growth in Phillipines - Putri, Rizha Claudilla; Azani, Adila (Reformasi Hukum, 2025)
Foreign direct investment (FDI) plays a pivotal role in fostering economic growth, particularly in developing economies such as the Philippines. While much of the literature emphasizes economic determinants of FDI, limited research has examined the interaction between law and economics in shaping investment sustainability. This study adopts a descriptive qualitative approach, combining doctrinal legal research with economic analysis, to investigate how regulatory certainty, institutional frameworks, and dispute settlement mechanisms influence FDI inflows. Drawing on primary sources such as the Foreign Investments Act of 1991, bilateral investment treaties, and international arbitral decisions, as well as secondary data from UNCTAD, the World Bank, and the Bangko Sentral ng Pilipinas, the research explores the legal and economic dynamics of FDI from 2000 to 2025. Findings reveal that while economic reforms and comparative advantages have driven FDI growth in the Philippines, legal certainty and compliance with international investment norms remain critical in sustaining investor confidence. This dual analysis underscores that inclusive and sustainable growth can only be achieved when foreign investment is supported by transparent legal frameworks, effective dispute resolution, and alignment with international obligations. The article contributes to bridging the gap between economic studies and legal discourse on FDI, offering recommendations for strengthening regulatory mechanisms to enhance the Philippines’ long-term investment climate.